Commodity market controls : a historical review - Nappi, Carmine (Lexington, Mass. : Lexington Books, 1979)
This book provides a historical review of the commodities market globally from 1914 to 1977. It examines commodities like wheat, tin, sugar, coffee, cocoa. Others include copper, bauxite, iron ore and mercury.
Includes index.
lje 16/06/17
Loans
Keywords: Commodity control---History.